Geochemical stability of reclaimed coal mine waste dump: Implications for pit lake water quality and post-mining landscape utilization - Triwibowo, Didik; Elma, Muthia; Suhartono, Eko; Riduan, Rony; Noor, Ihsan (Brawijaya University, 2026)
Open-pit coal mining operations require the removal of overburden and the creation of waste dump piles. Waste dump management must consider the classification of the material, specifically whether it is Potentially Acid-Forming (PAF) or Non-Acid-Forming (NAF), based on its geochemical characteristics. This paper examined the geochemical stability of a 10-year-old coal mining overburden waste dump in Paringin, South Kalimantan, which has since been revegetated. Samples were taken from the upstream and downstream sections of the catchment area, based on the NAF homogeneous type of overburden moved to the waste dump area during the reclamation process. This was achieved by creating a soil profile to a depth of 120 cm, resulting in nine samples for each soil profile. The analysis results in the upstream and downstream sections suggested the capacity to neutralize acid. The conclusion was that the overall waste dump has stable geochemical conditions with lower acid mine drainage generation, as represented by a negative NAPP, due to the presence of adequate ANC to neutralize acidity from the Sulfur content in the upstream section and low total Sulfur in the downstream section. The geochemical stability of the waste dump, which is NAF, has a significant influence on the water quality of Paringin Pit Lake, where all surface water from the catchment area flows. These results indicated that no AMD generation occurs in the water of Paringin Pit Lake. With no potency for AMD generation, the overall post-mining landscape could have potential future utilization.